You cannot miss it: Pancreatic mucoepidermoid carcinoma. Issue 11 (March 2018) - Hu, Hai-Jie; Zhou, Rong-Xing; Liu, Fei; Wang, Jun-Ke; Li, Fu-Yu
Abstract: Rationale: Pancreatic mucoepidermoid carcinoma (MEC) is a rare disease with no more than 10 cases reported in literature. The prognosis is poor and few patients can survival more than 1 year. Patient concerns: We presented a case of patient manifested as left upper abdominal pain. Computed tomography demonstrated a low-density shadow measuring 2.1 × 2.4 cm situated at the transition area of neck and body of the pancreas with obscure boundary and irregular enhancement. The preoperative symptoms and imaging features were unspecific. Diagnoses: Pancreatic MEC. Interventions: Curative surgery of distal pancreatectomy was conducted. Postoperatively, the patient subsequently underwent 8 cycles of chemotherapy using cisplatin (25 mg/m 2 ) on day 1 to day 3; and gemcitabine (1000 mg/m 2 ) on day 1 and day 8, repeated every 21 days. Outcomes: The patient was monitored on a regular basis at our outpatient department and survived 23 months after surgery. Lessons: Preoperative diagnosis of pancreatic MEC is difficult. Patients with pancreatic MEC may have a survival benefit from the multimodal treatment of curative surgery combined with chemotherapy.